Cell Senescence in Myxoid/Round Cell Liposarcoma. (24th June 2014) - Kåbjörn Gustafsson, Christina; Ståhlberg, Anders; Engtröm, Katarina; Danielsson, Anna; Turesson, Ingela; Åman, Pierre
Abstract : Myxoid/round cell liposarcoma (MLS/RCLS) is the second most common liposarcoma type and characterized by the fusion oncogenes FUS-DDIT3 or EWSR1-DDIT3 . Previous analysis of cell cycle regulatory proteins revealed a prominent expression of G1-cyclins, cyclin dependent kinases, and their inhibitors but very few cells progressing through the G1/S boundary. Here, we extend the investigation to proteins involved in cell senescence in an immunohistochemistry based study of 17 MLS/RCLS cases. Large subpopulations of tumor cells expressed the RBL2 pocket protein and senescence associated heterochromatin 1 γ and IL8 receptor β . We conclude that MLS/RCLS tissues contain major populations of senescent tumor cells and this may explain the slow growth rate of this tumor type.